2019
DOI: 10.1051/0004-6361/201833564
|View full text |Cite
|
Sign up to set email alerts
|

The LOFAR Two-metre Sky Survey

Abstract: The LOFAR Two-metre Sky Survey (LoTSS) is an ongoing sensitive, high-resolution 120–168 MHz survey of the northern sky with diverse and ambitious science goals. Many of the scientific objectives of LoTSS rely upon, or are enhanced by, the association or separation of the sometimes incorrectly catalogued radio components into distinct radio sources and the identification and characterisation of the optical counterparts to these sources. We present the source associations and optical and/or IR identifications fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 55 publications
1
90
0
Order By: Relevance
“…The remaining 6 sources lack either the resolution or extended emission required to determine if such conditions exist. While follow up observations would be required to robustly confirm such structure, preliminary exploration of the LOFAR Two Meter Sky Survey value added catalogue (LoTSS; Shimwell et al 2019;Williams et al 2019) using the automated morphological classification of Mingo et al (2019) suggests that those sources where structure can be confidently identified contain similar morphological features to those presented here. It is therefore likely that this orientation based explanation can be extended to explain a significant fraction of hybrid population.…”
Section: The Hybrid Morphology Populationmentioning
confidence: 70%
“…The remaining 6 sources lack either the resolution or extended emission required to determine if such conditions exist. While follow up observations would be required to robustly confirm such structure, preliminary exploration of the LOFAR Two Meter Sky Survey value added catalogue (LoTSS; Shimwell et al 2019;Williams et al 2019) using the automated morphological classification of Mingo et al (2019) suggests that those sources where structure can be confidently identified contain similar morphological features to those presented here. It is therefore likely that this orientation based explanation can be extended to explain a significant fraction of hybrid population.…”
Section: The Hybrid Morphology Populationmentioning
confidence: 70%
“…We use v1.0 of the value-added catalogue for the HETDEXarea data release of LoTSS. The first step in creating the value-added catalogue involved using PyBDSF 1 to produce a radio source catalogue for the field, after which a decision tree was used to further categorise the sources, with details provided in (Williams et al 2019). After filtering the 325,694 sources to only include those classified as resolved leaves 24,096 sources (Shimwell et al 2019).…”
Section: Source Cutoutsmentioning
confidence: 99%
“…The LoTSS association and cross-identification effort (Williams et al 2019) was a project in which expert astronomers were tasked with characterising the radio emission for sources larger than 15 . Indicated were the locations of the peaks and extents of the emission, and whether there was one or more sources present.…”
Section: Classificationsmentioning
confidence: 99%
See 2 more Smart Citations